(untitled) (New York, NY., 2003)
This unique reference describes the preparation of ferments and utilization of starters in the commercial baking and food industries—offering in-depth discussion on the modification of sourdough processes in the production of common bakery products, as well as the microbiological principles, fermentation pathways, product formulations, and technological methodologies relating to these procedures.
Keywords: Fermention,Biotechnology